Analysis of Nurse Performance in Improving the Quality of Hospital Services - Wahyuningsih, Luh Gde Nita Sri; Susanti, NLP Dina; Mahardika, I Made Rai (Babali Publisher, 2024)
Background: Nurse performance is one measure of the quality of services provided in hospitals which will indirectly influence patient satisfaction. Objective: This study aims to analyze the performance of nurses in providing nursing care and to determine the relationship between nurse performance and service quality. Method: The research design used was descriptive correlation to determine the relationship between nurse performance and service quality. The research instrument uses a questionnaire given via Google Form with two answer choices yes and no. The sample was calculated using the Slovin formula so that a sample size of 130 people was obtained plus a 10% chance of dropping out, resulting in 143 people from 193 nurses as population. Result: The research results showed that good nurse performance can provide good quality service, namely 130 people (91%). Meanwhile, poor nurse performance will result in poor service quality for 7 people (4.9%). The statistical test results using the Chi Square test were p=0.003, Conclusion: There is a relationship between nurse performance and service quality. Performance is one indicator of the quality of service in a hospital